First Workshop for Detection of Heparin-induced Antibodies: Validation of the Heparin-induced Platelet-activation Test (HIPA) in Comparison with a PF4/Heparin ELISA - Eichler, P.; Budde, U.; Haas, S.; Kroll, H.; Loreth, R. M.; Meyer, O.; Pachmann, U.; Pötzsch, B.; Schabel, A.; Albrecht, D.; Greinacher, A. (Thrombosis and Haemostasis, 1999)
Background. No data exist regarding the inter-laboratory reproducibility of the heparin-induced-platelet-activation (HIPA) test, the most widely used functional assay in Germany for the detection of heparin-induced thrombocytopenia (HIT) antibodies. Methods. Nine laboratories used an identical protocol to test eight different sera with the HIPA test. Five laboratories also tested the sera with a platelet factor 4 (PF4)/heparin-complex ELISA. Cross-reactivity with danaparoid-sodium was assessed using 0.2 aFXa units instead of heparin in the HIPA test. Results. Two of nine laboratories had no discrepant HIPA test results. Four laboratories differed in one sample, one reported two discrepant results, and two laboratories reported more than two discrepant results. Cross-reactivity with danaparoid-sodium test results differed among laboratories. PF4/heparin ELISA results were identical in all five laboratories. Conclusion. The HIPA test requires strict quality control measures. Using both a sensitive functional assay (HIPA test) and a PF4/heparin ELISA will allow detection of antibodies directed to antigens other than PF4/heparin complexes as well as detection of IgM and IgA antibodies with PF4/heparin specificity.